Addressing role and value in policing: toward a sustainable policing framework. Issue 2 (18th May 2015) - Caputo, Tullio; McIntyre, Michael Louis
Abstract : Purpose: – The purpose of this paper is to examine the sustainability of policing organizations and propose approaches to enhance their sustainability. Design/methodology/approach: – This paper uses an action research approach involving the researchers and partners from the main national policing bodies in Canada and six police service research sites. Findings: – This paper presents a Sustainable Policing Framework (SPF) intended to enhance the sustainability of policing services. Practical implications: – The SPF the authors present can be implemented by police service organizations to assist with organizational development as the external environment changes. Originality/value: – No other approaches to police sustainability that involve a framework similar to the one that is presented are known. This paper provides specific tools for police services to deploy to address their sustainability concerns.